Habitation, Urban Context and Psychosocial Rehabilitation - Rodrigues , Bruna Mota; Santos , Mauro César de Oliveira; Bursztyn , Ivani (Revista Nacional de Gerenciamento de Cidades, 2021)
This paper articulates architecture, urbanism and mental health through the study of specific habitation, called Therapeutic Residences, for people with severe mental illness who undergo psychosocial rehabilitation. The study analyzes the insertion of these habitations in the urban scheme, in relation to the possibilities of social coexistence, access to commerce, services and other public equipment through the presentation of two case studies located in the west zone of the city of Rio de Janeiro. Besides the considerations linked to the urban space in its physical sense, it also touches on the subjective questions inherent to the exchanges and experiences possible in this context. The methodological strategies correspond to the survey and data analysis along with a qualitative approach. Information made available by City Hall and Mental Health Office, satellite images, semi-structured interviews directed to professionals involved in assisting at the Therapeutic Residences and, in the case of the habitants, open interviews were used. The results indicate the offer of services, the location and the relation of the houses with the street as fundamental factors to the stimulus of social coexistence. It is concluded that the closed condominium model exclusive to TR, in addition to the fragility and difficulties in the urban area in which it is inserted, it hinders the process of psychosocial rehabilitation and it still refers to the idea of an asylum institution. The model of a one-story house integrated to the consolidated urban fabric suggests more possibilities of creating community ties and appropriating the urban space.